2019
DOI: 10.1155/2019/9896410
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Heat on Health and Productivity among Maize Farmers in a Tropical Climate Area

Abstract: Background. Heat stress disorders may cause negative health outcome and subsequent productivity reduction especially in those who work under direct sunlight for an extended number of hours. Objective. This study assessed the impact of heat on the health and productivity among maize farmers in a hot tropical country. Methods. A cross-sectional study was conducted among 396 maize farmers, randomly selected across Gombe province, Nigeria. The wet bulb globe temperature monitor (WBGT) Model QuesTemp036 was used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…The most common heat-related health outcome assessed was HRI (n = 57; 62%). Twenty-seven out of 57 of these studies relied on selfreported HRI symptoms (25,27,30,(40)(41)(42), while 21 measured various physiological parameters such as core body temperature, skin temperature, heart rate, blood pressure, changes in body weight, or urine specific gravity (61,68,(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88). Another commonly assessed heat-related health outcome was kidney disease (n = 28; 30%).…”
Section: Descriptive Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common heat-related health outcome assessed was HRI (n = 57; 62%). Twenty-seven out of 57 of these studies relied on selfreported HRI symptoms (25,27,30,(40)(41)(42), while 21 measured various physiological parameters such as core body temperature, skin temperature, heart rate, blood pressure, changes in body weight, or urine specific gravity (61,68,(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88). Another commonly assessed heat-related health outcome was kidney disease (n = 28; 30%).…”
Section: Descriptive Characteristics Of Included Studiesmentioning
confidence: 99%
“…Heat-related Illnesses (HRI) are the most common health effects experienced by agricultural workers as a result of their prolonged exposure to high temperatures (30,(40)(41)(42). HRI are a continuum of diseases, ranging from mild symptoms such as heavy sweating, dizziness, fatigue, vomiting, headaches, and muscle cramps to more severe conditions such as lifethreatening heat strokes (12).…”
Section: Introductionmentioning
confidence: 99%
“…They also recognized that, even though there were adaptation strategies for coping with heat stress in Baku East in Northern Ghana, these strategies were ineffective. In their study of the impact of heat on health and productivity among maize farmers in the Gombe province of Nigeria, Sadiq, Hashim [65] found that farmers were frequently exposed to heat stress-a condition that was contributing to heat exhaustion and productivity decreases among small-holder producers.…”
Section: The Geographical Distribution Of Maximum Wbgtmentioning
confidence: 99%
“…Due to intensified global warming in recent years, extreme summer heat events tend to be frequent across the country. When the WBGT temperature exceeds 30°C, work ability will be reduced and serious health problems, such as heat stroke, muscle cramps, and even death, may occur (Sadiq et al, 2019). Moderate or very hot conditions may cause a 3%-12% reduction in work time of indoor workers (Xia et al, 2018).…”
Section: Analysis Of the Impact Of Rising Average Summer Temperatures On Wage Growthmentioning
confidence: 99%